Case Report: Successful treatment of severe pneumocystis carinii pneumonia in a case series of primary nephrotic syndrome after receiving anti-CD20 monoclonal antibody therapy - Liu, Lili; Zheng, Weihua; Wang, Ping; Wu, Ying; Zhu, Guanghua; Yang, Rong; Gu, Li; Huang, Wenyan; Kang, Yulin (Frontiers in Pediatrics, 2023)
Rituximab is emerging as a new steroid sparring agent in children with difficult-to-treat nephrotic syndrome due to its ability of depleting CD20-positive B cells. Life-threatening adverse events such as pneumocystis carinii pneumonia may occur even though it seems to be well tolerated. Since rituximab is wildly used in immune-mediated diseases, it is important to manage its severe adverse events. To explore the importance of early diagnosis and treatment of pneumocystis carinii pneumonia in children with primary nephrotic syndrome (PNS) after receiving rituximab therapy, we retrospectively analyzed the clinical data of PNS patients younger than 18 years old with pneumocystis carinii pneumonia who were hospitalized in our center. Clinical features and laboratory test results were retrieved from the electronic medical records. Severe pneumocystis carinii pneumonia occurred in one child with steroid resistant nephrotic syndrome and two with steroid dependent nephrotic syndrome patients after rituximab treatment. These patients were diagnosed in time by metagenomic next-generation sequencing (mNGS) for pathogen detection. Fortunately, all three patients survived after anti-fungal treatment and achieved complete remission eventually. In conclusion, early diagnosis by using mNGS and timely antifungal treatment is the key to successful management of pneumocystis carinii pneumonia in children with difficult-to-treat PNS.